Changes in biometry and cerebroplacental hemodynamics in fetuses with congenital heart diseases - Peixoto, Alberto Borges; Tonni, Gabriele; Júnior, Edward Araujo (Journal of Thoracic Disease, 2016)
Multiple factors can influence fetal blood flow, including placental function, heart anatomy and distal vascular bed impedance (1). Nutrients and oxygen undergo exchange between fetal and maternal circulation at the level of placental villi. Placenta extracts a fixed proportion of the nutrient stream (70% of glucose and 40% of oxygen supplied to the uterus) whereas fetal nutrition is restricted to the surplus that remains after placental demands (2).